2016
DOI: 10.4238/gmr.15027880
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the vascular endothelial growth factor (VEGF) gene associated with asthma

Abstract: ABSTRACT. It has been proven that vascular endothelial growth factor (VEGF) is involved in airway restoration and the development of asthma. We sought to examine the relevance of VEGF gene polymorphisms to asthma in the Chinese Han population. We extracted the whole genomic DNA from the peripheral blood of 471 participants, including 226 patients with asthma and 245 healthy controls. Seven single nucleotide polymorphisms (SNPs) of the VEGF gene were genotyped using the MassARRAY system. The data were then anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…These studies utilize a number of techniques that include, but are not limited to, agarose gel electrophoresis, restriction fragment length polymorphism (RFLP), real time/polymerase chain reaction (RT/PCR), Sanger-sequencing and microarrays. Whole blood is the primary source of genomic DNA in most of the clinical investigations associated with genetics, genomics, pharmacogenomics, genetic diseases and epidemiology (Gao et al, 2015, Lu et al, 2016, Rzehak et al, 2016, Visvikis et al, 1998). Buccal swab or saliva is also used to extract DNA for a number of PCR based studies (Küchler et al, 2012, Ng et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These studies utilize a number of techniques that include, but are not limited to, agarose gel electrophoresis, restriction fragment length polymorphism (RFLP), real time/polymerase chain reaction (RT/PCR), Sanger-sequencing and microarrays. Whole blood is the primary source of genomic DNA in most of the clinical investigations associated with genetics, genomics, pharmacogenomics, genetic diseases and epidemiology (Gao et al, 2015, Lu et al, 2016, Rzehak et al, 2016, Visvikis et al, 1998). Buccal swab or saliva is also used to extract DNA for a number of PCR based studies (Küchler et al, 2012, Ng et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that the diagnosis of asthma was positively associated with T alleles in the rs3025020 and rs3025039 single-nucleotide polymorphisms (SNPs) of the VEGF gene in the Chinese population [27]. There is also a report suggesting a borderline association between the G allele of the VEGF gene polymorphism at position -634 G/C and diagnosis of asthma in Tunisian children.…”
Section: Resultsmentioning
confidence: 99%
“…VEGF, an important regulator of angiogenesis and vascular remodelling, belongs to the platelet-derived growth factor family and is expressed in tissues rich in blood vessels, such as the lung tissue, and in inflammatory cells, including neutrophils, lymphocytes, monocytes and eosinophils (Lu et al, 2016). VEGF family members include VEGF-A, VEGF-B, VEGF-C, VEGF-D, VEGF-E, VEGF-F and placental growth factor (PIGF) (Melincovici et al, 2018).…”
Section: Discussionmentioning
confidence: 99%